Environmental Impacts of Dam Reservoir Filling in the East Amazon - da Silva, Geison Carlos Xisto; Medeiros de Abreu, Carlos Henrique; Ward, Nicholas D.; Belúcio, Liana Pereira; Brito, Daímio Chaves; Cunha, Helenilza Ferreira Albuquerque; da Cunha, Alan Cavalcanti (Frontiers in Water, 2020)
Mitigating the environmental impacts caused by hydroelectric dams is a worldwide challenge. Aquatic ecosystems are most impacted during the reservoir filling phase, yet water quality and biogeochemical dynamics are not well-studied at this stage. Here we evaluate water quality and hydraulic parameters in the Araguari River (Amapá, Brazil) during the filling of the Ferreira Gomes Hydroelectric Power Plant reservoir (HPPFG). The following key variables were monitored along with 19 other physical and chemical variables: Trophic State Index (TSI), Total Coliform (TC), E. coli (EC) and Chlorophyll-a (Chl-a). The following hydraulic-operational variables were also investigated: inflows (Qa), outflows (Qd), and variation in reservoir volume (Vol%). Multiple Regression Analyses showed that the key parameters were both significantly influenced by physio-chemical and hydraulic variables. Dissolved oxygen levels showed significant spatial variation, likely due to influence of turbulence from two other hydropower complexes upstream of the HPPFG reservoir. Vol% influenced TSI, which ranged from oligotrophic to hypertrophic and eventually stabilized at mesotrophic. Levels of TSI, TC, and Chl-a decreased and the level of E. coli increased as a function of Vol%. Cluster Analysis showed the formation of three spatial groups—two inside the reservoir and one downstream. This suggests that in the rainy season or transition season, the hydraulic residence time in the reservoir is very low (16-36 hr) when hydrodynamic processes are dominant. In the dry season residence times of roughly 1 month suggest that biogeochemical (e.g., nutrient utilization) and hydrodynamic processes occur at similar time scales. Overall, results from this study confirm the hypothesis that the filling phase has significant impacts on the key parameters of the water quality, which were at times above legal limits. We conclude that the filling phase generated environmental impacts and their repercussions should be considered in environmental assessment of future hydropower developments.